Analysis the Influence of Motivation, Work Environment, Workplace Spirituality, and Leadership Style on Organizational Citizenship Behavior (OCB), with Job Satisfaction as a Mediating Factor, among Employees in Beauty Clinics in the City of Batam - Priscilla, Yuddy Giovanna; Maharani, Delby; Muchsinati, Evi Silvana (Rescollacom (Research Collaborations Community), 2024)
This research aims to explore the influence of motivation, work environment, workplace spirituality, and leadership style on Organizational Citizenship Behavior (OCB), with job satisfaction as the mediating variable, among employees in beauty clinics in Batam City. The study adopts a quantitative approach, collecting primary data through Likert-scale questionnaires distributed via Google Form to employees in beauty clinics in Batam City. Secondary data is sourced from official channels such as journals, government websites, and national news. Data analysis employs Partial Least Square (PLS) to test hypotheses and the research model. The research population comprises 132 respondents, with a minimum sample size of 100 respondents determined through Krejcie and Morgan's calculation using simple random sampling. The research findings indicate: 1) a significant positive correlation between the work environment and OCB mediated by job satisfaction (t-statistic: 2.992, p-value: 0.003); 2) a significant positive correlation between leadership style and OCB mediated by job satisfaction (t-statistic: 2.664, p-value: 0.008); 3) a significant positive correlation between job satisfaction and OCB (t-statistic: 25.974, p-value: 0.00); 4) no significant correlation between motivation and OCB mediated by job satisfaction (t-statistic: 0.531, p-value: 0.596); 5) no correlation between workplace spirituality and OCB mediated by job satisfaction (t-statistic: 0.689, p-value: 0.491) among employees in beauty clinics in Batam City.